PERAN KEPUASAN PELANGGAN DALAM MEMEDIASI PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN - Wiryana, Kadek Velia Sita Devi; Asti Aksari, Ni Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.07.TAHUN.2023DO - 10.24843/EEB.2023.v12.i07.p07, 2023)
Customer loyalty is one of the important assets that must be considered by the company. Customer loyalty is created through customer satisfaction with the quality of services offered. This study aims to analyze the effect of customer satisfaction, which mediates service quality, on customer loyalty. This research is located in Badung Regency, with a sample size of 110 respondents who have used the services of Salon Tria more than once, using a purposive sampling method, and distributed using a Google Form Questionnaire, measured by 11 indicators using the Likert Scale. The data analysis techniques used are path analysis, the Sobel test, and the VAF test. The results of this study indicate that all hypotheses are accepted. Service quality has a positive and significant effect on customer loyalty, service quality has a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant effect on customer loyalty, according to the findings of this study, costomer satisfaction acts as a moderation in the relationship between service quality and customer loyalty. in order to increase customer loyalty, it can be done through improving service quality and customer satisfaction